2019
DOI: 10.1111/jch.13667
|View full text |Cite
|
Sign up to set email alerts
|

Body fat percentage, obesity, and their relation to the incidental risk of hypertension

Abstract: Studies have indicated that increased body fat is associated with cardiovascular risk factors including hypertension. However, there is only limited information about the influence of body fat percentage (BF%) on incident hypertension. In a cohort of Korean genome epidemiology study (KoGES), 4864 non‐hypertensive participants were divided into 5 quintile groups, and followed‐up for 10 years to monitor incident hypertension. Cox proportional hazard model was used to evaluate the hazard ratio (HRs) and 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
3
20
0
4
Order By: Relevance
“…The study by Park et al validates previously reported information on the importance of measuring BF% even in non‐obese individuals to detect those who have an increased risk of developing hypertension, in a Korean population. The confirmation of this association should be a point of interest for considering its implementation in routine clinical practice and to be taken into account in future guidelines.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…The study by Park et al validates previously reported information on the importance of measuring BF% even in non‐obese individuals to detect those who have an increased risk of developing hypertension, in a Korean population. The confirmation of this association should be a point of interest for considering its implementation in routine clinical practice and to be taken into account in future guidelines.…”
supporting
confidence: 82%
“…One of the main points of the study by Park et al is the long follow‐up period, ie, 10 years, but also the finding that high BF% was significantly associated with the increased risk of incident hypertension even in individuals with low BMI, WC, and WHR. This underlies the importance of globally assess adiposity in general population, independently of “apparent” normal weight.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early identification and control of individuals suffered from hypertension were, therefore, critical for improving the quality of life and reducing mortality in a high-risk population. Body fat percentage (BFP), as a more accurate and reliable indicator for evaluating general obesity compared to BMI, cannot be neglected (11,12). Briefly, a previous study performed in southern Brazil showed that compared to individuals with lower BFP, individuals who were with higher BFP were prone to have a greater risk of hypertension (13).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Jiang et al also reported that BFP was a better indicator for discriminating hypertension, regardless of gender (14). Recently, research conducted in South Korea indicated that increased BFP was associated with the high risk of hypertension even in non-obese subjects (12). However, Alvin Chandra et al found that neither total nor subcutaneous adiposity was related to the onset of hypertension (15).…”
Section: Introductionmentioning
confidence: 99%